Nutritive Evaluation Of Sago Fibre As Feedstuff For Sheep - Yadav, Devendra Prasad (1990)

(untitled)
Nutrient evaluation of sago fibre showed that the fibre has same potential and could be utilized. as feed for ruminants. however, as a source of nutrients, it has limitations arising from low intake, digestibility, crude protein and. essential minerals content. The present study shower that sago fibre was low in crude protein (CP) (3.3%) am high in neutral detergent fibre (NDF) (72.5%) am acid detergent lignin (ADL) (25.8%) con tent. Treatment of sago fibre with 0,2,4 and 6% urea increased the CP content of the fibre from 3.3 to 10.4, 13.4 and 16.7% and decreased the NDF content (%) from 72.5 to 63.2, 62.3 am 60.8, respectively. Sodium hydroxide treatment of sago fibre decreased the NDF content, and also resulted in reduced CP content (2.9%) . may be due to chemical degradation of the protein into volatile compounds. Both urea and sodium hydroxide treatment had no effect on other cell wall component.